Examining gender as an issue of policy priority: a case study of four Kenyan health policy implementation strategies - Odero, Henry Owoko; Kwesiga, Doris; Odunga, Sally; Kadengye, Damazo T.; Kiwuwa-Muyingo, Sylvia (Frontiers in Public Health, 2025)
BackgroundDespite global and national commitments to gender equity, including Sustainable Development Goal 5, health policy processes often fail to adequately integrate gender considerations. This study explores how gender is prioritized in the development and implementation of four Kenyan Health Policy Implementation Strategies (HPIS), offering insight into the role of institutional actors, policy framing, and contextual factors.MethodsA qualitative case study was conducted involving content analysis of four HPIS documents - KASF II 2020, NSP-NCD 2021, NSP-TB 2019, and COVID-TTS 2019 - and semi-structured interviews with 16 policy stakeholders. Data were analyzed using the Shiffman and Smith framework, which examines actors, ideas, policy environments, and issue characteristics influencing policy prioritization.ResultsGender prioritization varied among the policies under review. In the KASF II 2020, strong leadership from organizations such as the National AIDS Control Council (NACC), UNAIDS, and UNDP effectively drove gender integration. These actors successfully advocated for gender-responsive metrics and policies, supported by robust gender-disaggregated data. The policy framing (ideas) clearly recognized HIV as inherently gendered, emphasizing differentiated impacts across gender groups. The favorable policy environment, including alignment with Kenya’s Universal Health Coverage under the “Big Four Agenda,” enabled gender mainstreaming. Conversely, the NSP-NCD 2021 acknowledged gender primarily through a vulnerability lens, identifying gender-specific behaviors such as higher tobacco use among men. However, outdated data and limited structural guidance restricted the practical application of gender-specific strategies. The NSP-TB 2019 strategy on the other hand exhibited minimal gender integration due to the absence of dedicated gender advocacy actors and ambiguity in policy framing regarding gender as a social versus biological issue. The COVID-TTS was rapidly developed in response to the pandemic emergency, initially neglecting gender considerations entirely. Later, as gender disparities became apparent, the policy environment shifted slightly toward acknowledging these disparities, but actions remained largely reactive and inconsistent.ConclusionEffective gender integration in Kenyan health policies depended significantly on active leadership by key actors, strategic framing of gender issues, a conducive policy environment, and reliable gender-specific data. Strengthening these elements is key in improving future gender responsiveness in health policy.